Enhancement in the field emission behavior of graphene in N-2/O-2 high vacuum ambience - Suryawanshi, S. R.; Kolhe, Pankaj S.; Gavhane, D. S.; Patil, S. S.; Chavan, P. G.; More, Mahendra A.; Late, Dattatray J. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Herein we report, pressure dependent field emission (FE) behaviour of a few-layer graphene emitter. Gas dependent FE properties have been investigated in ultra high vacuum (UHV), as well as in N-2 and O-2 ambience at base pressure similar to 1x10(-6) torr. Interestingly, the graphene emitter when operated in N-2/O-2 ambience exhibits lower turn-on field and higher emission current density, as compared to the UHV conditions. The emission current stability investigated at preset value of similar to 1 mu A over the period of more than 2 hrs is found better in the N2 ambience and is characterized by fewer fluctuations, in contrast to the behaviour in the O-2 ambience. The observed enhanced electron emission behavior in N-2/O-2 ambience is attributed to modulation of the work function of graphene emitter.
Keywords: graphene; Pressure Dependent Field Emission

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets